Standard Methods for Sampling Freshwater Fishes: Opportunities for International Collaboration. Issue 3 (8th March 2017) - Bonar, Scott A.; Mercado‐Silva, Norman; Hubert, Wayne A.; Beard, T. Douglas; Dave, Göran; Kubečka, Jan; Graeb, Brian D. S.; Lester, Nigel P.; Porath, Mark; Winfield, Ian J.
Abstract : With publication of Standard Methods for Sampling North American Freshwater Fishes in 2009, the American Fisheries Society (AFS) recommended standard procedures for North America. To explore interest in standardizing at intercontinental scales, a symposium attended by international specialists in freshwater fish sampling was convened at the 145th Annual AFS Meeting in Portland, Oregon, in August 2015. Participants represented all continents except Australia and Antarctica and were employed by state and federal agencies, universities, nongovernmental organizations, and consulting businesses. Currently, standardization is practiced mostly in North America and Europe. Participants described how standardization has been important for management of long‐term data sets, promoting fundamental scientific understanding, and assessing efficacy of large spatial scale management strategies. Academics indicated that standardization has been useful in fisheries education because time previously used to teach how sampling methods are developed is now more devoted to diagnosis and treatment of problem fish communities. Researchers reported that standardization allowed increased sample size for method validation and calibration. Group consensus was to retain continental standards where they currently exist but to further explore international and intercontinental standardization, specifically identifying where synergies and bridges exist, and identify means to collaborate with scientists where standardization is limited but interest and need occur.